COVID-19 vaccines in elderly subjects: Considerations on efficacy and safety - Marco Bongiovanni (Archives of Clinical Gastroenterology - Peertechz Publications, 2021)
The SARS-CoV-2 pandemic dramatically involved elderly subjects, causing a very high number of deaths in this specific population, with a risk of mortality reaching 50% in subjects older than 80 years [1-3]. As a consequence, as the world prepares for a mass campaign to vaccinate as many people as possible in the shortest time, older and frailty individuals have been recognized as categories to be vaccinated first. Several countries assessed that it was mandatory to work on vaccine campaigns in these groups of patients, therefore elderly patients and residents in care homes were among the first group of individuals to be vaccinated [4]. But what is the evidence that the vaccines are safe and effective in this population? This paper reviews the vaccine currently available, with a particular focus on the evidence of their safety and efficacy in the older population.